Rogue money and the underground economy an encyclopedia of alternative and cryptocurrencies - Edmunds, John C. 1947- (Greenwood, 2020)
"This easy-to-use guide covers the history, development, and current workings of cyber currencies and the underground economy, both in the United States and around the world"--Provided by publisher.